Comparative coronary anatomy in six twin pairs with coronary artery disease. Issue 1 (1st January 2000) - Frings, A M; Mayer, B; Böcker, W; Hengstenberg, C; Willemsen, D; Riegger, G A J; Schunkert, H
Abstract : OBJECTIVE: To compare the coronary anatomy and the location of coronary lesions in monozygotic and dizygotic twin pairs affected with coronary artery disease. DESIGN: Coronary angiographic findings were compared with respect to the distribution of coronary blood supply and the location of coronary lesions. MAIN OUTCOME MEASURES: Distribution of coronary blood supply, diameters and length of proximal coronary arteries. RESULTS: The lumen diameters of the left main coronary artery, the left anterior descending coronary artery, the circumflex artery, and the right coronary artery, as well as the lengths of the left main coronary artery, showed similar variability within monozygotic and dizygotic twin pairs. With respect to the dominance pattern of coronary blood supply, two of three monozygotic twin pairs differed, while all dizygotic twin pairs were concordant. Concordant and discordant locations of stenoses were found with similar frequency in monozygotic and dizygotic twin pairs. CONCLUSIONS: The dominance pattern of coronary blood supply and the location of coronary lesions are not strictly hereditary. The high concordance of premature coronary artery disease found in monozygotic twin pairs may largely be related to factors that are independent of the macroanatomic distribution of the coronary blood supply.